"My social credo" - Maksimov, Grigorij Petrovič, 1893-1950 ([California?] : Boris Yelensky Book Fund, 1973)
"Gregory Maximoff was one of the most clear-thinking figures in the Russian anarchist movement, and the present essay constitutes a brief but foreceful statement of his social views."--Publisher's note.
Keywords: Revolutions and socialism; Anarchism; Capitalism; Communism